Analysis of the influence of ontogenetic time and prenatal hypoxia factors on the morphometric parameters of the specialized contact apparatus in the rat ventricular myocardium. - Petruk, N. S. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Cardiovascular diseases remain the main cause of death around the world and among Europeans and despite recent decreases in mortality rates in many countries they are still responsible for over 4 million deaths per year. The proportion of all deaths that are attributable to cardiovascular disease is substantially greater among women (52%) than men (42%). Prenatal hypoxia causes morphological and functional changes in the fetus and newborn and, in particularly, in the myocardium. That’s why the morphofunctional approach is crucial in the investigation of the effects of chronic prenatal hypoxia on the specialized contact apparatus in the rat ventricular myocardium. Objective. The aim of this study was to determine the influence of the ontogenetic time and prenatal hypoxia factors on the variance of the morphometric parameters of the specialized contact apparatus in the rat ventricular myocardium during ontogenesis. Methods. White rats were used as a material. Intrauterine hypoxia was modelled by intraperitoneal injection of sodium nitrite from 10th to 21st day of pregnancy. Tissue of different parts of the ventricular myocardium was used for electron microscopic examination by the standard method. Morphometric and statistical methods and one-way ANOVA were applied. Results. It was determined that influence of the ontogenetic time factor on the variance of the morphometric parameters of the desmosomes and fascia adherens was predominant during prenatal ontogenesis. For the majority of parameters of the gap junctions (3 of 4) the impact of the prenatal hypoxia factor was greater during this period. It was shown that after birth the influence of prenatal hypoxia factor on the variation of morphometric parameters of desmosomes, fascia adherens and gap junctions was predominant. The attention was paid to the influence of the hypoxic injury factor on the variance of the intermembranous space distance of the fascia adherens (92,8%; p<0,01). Quantitative parameters of intercalated disc to a greater extent dependent on the influence of ontogenetic time factor, indicating its morphogenesis just after birth. Conclusion. We compared the influence of the ontogenetic time and prenatal hypoxia factors on the morphometric parameters of the specialized contact apparatus and identified the main trends in their dynamics during ontogenesis.